The power and potential of genomics in weed biology and management. Issue 10 (12th June 2018) - Ravet, Karl; Patterson, Eric L; Krähmer, Hansjörg; Hamouzová, Kateřina; Fan, Longjiang; Jasieniuk, Marie; Lawton‐Rauh, Amy; Malone, Jenna M; McElroy, J Scott; Merotto, Aldo; Westra, Philip; Preston, Christopher; et al.
Abstract: There have been previous calls for, and efforts focused on, realizing the power and potential of weed genomics for better understanding of weeds. Sustained advances in genome sequencing and assembly technologies now make it possible for individual research groups to generate reference genomes for multiple weed species at reasonable costs. Here, we present the outcomes from several meetings, discussions, and workshops focused on establishing an International Weed Genomics Consortium (IWGC) for a coordinated international effort in weed genomics. We review the 'state of the art' in genomics and weed genomics, including technologies, applications, and on‐going weed genome projects. We also report the outcomes from a workshop and a global survey of the weed science community to identify priority species, key biological questions, and weed management applications that can be addressed through greater availability of, and access to, genomic resources. Major focus areas include the evolution of herbicide resistance and weedy traits, the development of molecular diagnostics, and the identification of novel targets and approaches for weed management. There is increasing interest in, and need for, weed genomics, and the establishment of the IWGC will provide the necessary global platform for communication and coordination of weed genomics research. © 2018 Society of Chemical Industry Abstract : There is increasing interest in, and need for, weed genomics. The International Weed Genomics Consortium will provide the necessary platform to globally coordinate weed genomics research.